Answer:
q+3/4r=p
Step-by-step explanation:
r=4/3(p-q)
Distribute the 4/3
r=4/3p-4/3q
Add 4/3q to each side
4/3q+r=4/3p
Multiply ALL variables by 3/4 (undoes the 4/3)
q+3/4r=p
Answer:
Josh is wrong.
Step-by-step explanation:
5^-x / 5^x = 5^(-x-x) = 5^-2x
= 1 / 5^2x
(you subtract the exponents when dividing )
So Josh is wrong ( he would be correct if we were multiplying)
Answer: you can ask questions your struggling with and people like me will help you answer them. You can also help other people answer their questions and get points for it
Step-by-step explanation:
Answer:
45
Step-by-step explanation: